Garcínía brasiliensis leaves: Bioactive properties and phytochemical assessment - Zan, Renato André (2018)
The Amazon rainforest is the home to several medicinal plant species popularly used for the treatment of a wide range of diseases. Despite the rich biodiversity of this region, there is still a lack of comprehensive studies regarding the uses, bioactivities, chemical composition and pharmacological properties of many of these medicinal plants [l]. In the present work, Garcinia brasiliensis Mart., a green plant native to the Amazon region, cultivated for its edible fruit, popularly referred to as "bacuparianão" or "guapomo" was studied. Some of its well reported bioactive properties include antioxidant, antidiabetic, anti-inflammatory, antispasmodic and antiprotozoal activities but very little studies have been conducted describing the phytochemical profile and establishing compounds-bioactivity relationships of the extracts obtained from its vegetative organs [2]. In view of these pharmaceutical potentials, leaves of G. brasilienses were collected at São Cristóvão site, Paraná, Brazil. They were then submitted to a cold methanol extraction, and further liquid-liquid partitioned to obtain hexane, dichloromethane and ethyl acetate fractions. The antioxidant, antiinflammatory, antimicrobial and cytotoxic activities of each fraction were tested, and the most bioactive fraction was submitted to phenolic characterization using HPLCDAD- ESI/MSn. The results showed that the ethyl acetate fraction showed the highest antioxidant activity which was comparable to Trolox, the positive control. This fraction also showed a broad spectrum antimicrobial activity against Gram-positive and Gramnegative bactéria, and Cândida albicans. The phenolic profile of the ethyl acetate fraction presented twelve flavonoids, being morelloflavone-7"-0-glucoside (52. 1±0.4 mg/g) and gardinia biflavonoid 2a glucoside (27. 5±0.2mg/g) the major compounds identified. These results indicate that leaves of G. brasiliensis might be a potential source of natural biomolecules for pharmaceutical and medicinal applications.